Uveitis in Tumor Patients Treated with Immunological Checkpoint- and Signal Transduction Pathway-Inhibitors. (17th November 2022) - Thurau, Stephan; Engelke, Hendrik; McCluskey, Peter; Symes, Richard J.; Whist, Eline; Teuchner, Barbara; Haas, Gertrud; Allegri, Pia; Cimino, Luca; Bolletta, Elena; Miserocchi, Elisabetta; Russo, Marinella; et al.
ABSTRACT: Purpose: New tumor therapies like immune checkpoint inhibitors and small molecule inhibitors of MEK and BRAF have increased the patient's survival rate but can be burdened with severe side-effects including uveitis. Here, we show the spectrum, treatment, and outcome of uveitis types induced by tumor treatment. Methods: In this retrospective study, we have included 54 patients from different centers who were developing uveitis under tumor therapy. A 16-item questionnaire was analyzed for type, treatment, and outcome of uveitis and type of tumor treatment, which we have correlated here. Results: Irrespective of the tumor treatment, most patients developed anterior uveitis. All patients received corticosteroids and some additional immunosuppressive treatments. Cessation of tumor therapy was necessary only in a minority of cases. Conclusions: Ocular autoimmunity should be differentiated from toxic effects of cancer treatment and timely recognized since it can be generally well controlled by anti-inflammatory treatment, preserving the patient's vision without cessation of the tumor treatment.